1999
DOI: 10.1007/s100530050511
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced manipulation of the size and shape of small metal particles: Towards monodisperse clusters on surfaces

Abstract: A novel experimental technique is presented for post growth narrowing of the size distribution of metal nanoparticles on dielectric substrates. In order to demonstrate the potential of the method, oblate Ag clusters with mean radii of R = 6 nm and broad size distributions were prepared under ultrahigh vacuum conditions on quartz substrates. Narrowing of the width of their size distribution was accomplished by irradiation with short laser pulses. The laser light excites plasmons in the particles, the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Recently, Stietz et al showed that the size distribution of Ag nanoparticles was narrowed by 40% by choosing the laser pulse frequency such that only the smallest and the largest particles selectively absorbed light. 10 El-Sayed et al reported shape changes of colloidal gold nanorods by femtosecond and nanosecond laser pulses. 11 More recently, Mirkin et al showed that silver nanospheres were converted to nanoprisms by conventional fluorescent light.…”
mentioning
confidence: 99%
“…Recently, Stietz et al showed that the size distribution of Ag nanoparticles was narrowed by 40% by choosing the laser pulse frequency such that only the smallest and the largest particles selectively absorbed light. 10 El-Sayed et al reported shape changes of colloidal gold nanorods by femtosecond and nanosecond laser pulses. 11 More recently, Mirkin et al showed that silver nanospheres were converted to nanoprisms by conventional fluorescent light.…”
mentioning
confidence: 99%
“…It should be noted that narrowing of the width of the particle‐size distribution has previously been demonstrated by irradiation of metal surfaces with short laser pulses 42. The mechanism proposed is that the photon beam excites plasmons in the metal particles, the frequency of which depends on the size and shape of the clusters.…”
Section: Resultsmentioning
confidence: 94%
“…They were able to vary the particle size of colloidal Pd between 0.55 and 4.5 nm using the salt reduction method. Size control has also been reported for the sonochemical decomposition method and c-radiolysis [173,194,195]. According to the literature on the process of nucleation and particle growth, the essential factors which control the particle size are the strength of the metal-metal bond [48], the molar ratio of metal salt, colloidal stabilizer, reduction agent [1,128,135,[176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193], the extent of conversion or the reaction time [128], the temperature applied [1,177,189], and the pressure [177].…”
Section: 6mentioning
confidence: 97%